2023
DOI: 10.1002/ecy.4188
|View full text |Cite
|
Sign up to set email alerts
|

Year effects drive beta diversity, but unevenly across plant community types

Chhaya M. Werner,
Truman P. Young,
Katharine L. Stuble

Abstract: Year of establishment can be a critical driver of plant communities with the establishment stage of community development particularly susceptible to factors including ambient rain, temperature, and other temporally variable drivers (e.g., seed and seedling predators). However, while year effects have been shown to drive community structure at local (patch) scales, it is yet unexplored how these within‐patch effects scale up to drive landscape‐level patterns of biodiversity. These dynamics are likely critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Our results suggest obvious 'year effects' (Werner et al, 2020;Werner, Young and Stuble, 2024) from interannual climate variability in the species composition outcomes after restoration that had greater impact than landscape effects on community assemblage. We found that these year effects were explained by soil temperature and moisture before and after planting .…”
Section: Discussionmentioning
confidence: 79%
“…Our results suggest obvious 'year effects' (Werner et al, 2020;Werner, Young and Stuble, 2024) from interannual climate variability in the species composition outcomes after restoration that had greater impact than landscape effects on community assemblage. We found that these year effects were explained by soil temperature and moisture before and after planting .…”
Section: Discussionmentioning
confidence: 79%